COMPARISON OF SELF ESTEEM LEVEL OF INDIVIDUAL WHO REGULARLY ATTEND FITNESS CENTERS WITH THOSE OF THE SPORTS MAIN DIFFERENT SPORTS BRANCHES - IBRAHIM, YOUSIF (Fırat Üniveristesi, 2018)
Bu araştırma, (futbol, basketbol, voleybol, tenis, yüzme ve kick boks gibi) farklı spor dallarındaki bireyler ile düzenli olarak fitness merkezlerine giden kişilerin özgüven düzeylerini karşılaştırmak amacıyla gerçekleştirilmiştir. Çalışma örneklemini fitness salonlarına giden 210 kişi ile, farklı spor dallarında faaliyet gösteren 147 sporcu oluşturmuştur. Bireylerin yaş, boy, kilo, öğrenim durumu, medeni durumu, aylık gelir düzeyleri, meslekleri, spor branşları gibi bilgileri hazırlanan kişisel bilgi formu ile tespit edilmiştir. Ayrıca katilimcilarin öz güven düzeylerini belirlemek için, araştırmada 5 li Likertten oluşan öz güven ölçeği kullanılmıştır. Elde edilen veriler SPSS 22 paket programı kullanılarak analiz edilmiştir. Araştırma sonucunda düzenli olarak fitness salonlarına giden bireylerin diğer spor branşlarındaki bireylere kıyasla özgüven düzeylerinin daha fazla olduğu tespit edilmiştir. Fitnes Salonlarına düzenli olarak devam eden bireylerin dışındaki spor branşları içerisinde en yüksek özgüven düzeyine Futbolcuların sahip olduğu belirlenmiştir. Ayrıca fitnes salonuna devam etme süresi olarak bir yıldır devam edenlerin daha uzun süre fitnes salonuna devam eden bireylerden daha yüksek özgüven düzeyine sahip oldukları tespit edilmiştir. Anahtar Kelimeler: Özgüven, Fitnes, Spor Dalları

This research was conducted to compare the level of self-confidence among individuals in different sports (such as football, basketball, volleyball, tennis, swimming and kick boxing) and those who regularly go to fitness centres. The study sample consisted of 210 athletes attending fitness centres and 147 athletes in various sports branches. Individuals' data such as age, height, weight, education status, marital status, monthly income levels, occupations, sports branches were gathered by questionnaire form. In addition, in order to determine the self-confidence levels of the participants, self-confidence scale consisting of 5 Likert scales were utilized in this research. The obtained data were analyzed using the SPSS 22 packet software program. The results of the research revealed that the individuals who attend the fitness centres on a regular basis had higher levels of self-confidence compared to the other sports branches. It was also found that the footballers have the highest level of self- confidence among the sports branches except those who regularly attend the fitness centres. Furthermore, the study unveiled that those who attend fitness centres for one year as the duration of the stay in the fitness centres have a higher level of self- confidence than individuals who attend the fitness centres for a longer period of time. Keywords: Self-confidence, Fitness, Sports branches
Düzenli olarak fitnes salonlarına devam eden bireylerin özgüven düzeylerinin farklı spor branşlarındaki sporcularla karşılaştırılması
Keywords: Spor